Internalized gay ageism, mattering, and depressive symptoms among midlife and older gay-identified men. (December 2015) - Wight, Richard G.; LeBlanc, Allen J.; Meyer, Ilan H.; Harig, Frederick A.
Abstract: Objective: In this paper we introduce the construct of "internalized gay ageism, " or the sense that one feels denigrated or depreciated because of aging in the context of a gay male identity, which we identify as an unexplored aspect of sexual minority stress specific to midlife and older gay-identified men. Methods: Using a social stress process framework, we examine the association between internalized gay ageism and depressive symptoms, and whether one's sense of mattering mediates or moderates this association, controlling for three decades of depressive symptom histories. The sample is 312 gay-identified men (average age = 60.7 years, range = 48–78, 61% HIV-negative) participating in the Multicenter AIDS Cohort Study (MACS) since 1984/85, one of the largest and longest running studies of the natural history of HIV/AIDS in the U.S., who provided contemporary (2012/13) reports of stress experiences. Results: We find that internalized gay ageism can reliably be measured among these men, is positively associated with depressive symptoms net of an array of other factors that may also influence symptomatology (including depressive symptom histories), and mattering partially mediates but does not moderate its effect on depressive symptoms. Conclusion: Midlife and older gay men have traversed unparalleled historical changes across their adult lives and have paved the way for younger generations of sexual minorities to live in a time of less institutionalized discrimination. Still, they are at distinct risk for feeling socially invisible and devalued in their later years. Highlights: Midlife and older gay men are subject to feeling depreciated and socially invisible. Internalized gay ageism is the confluence of ageism and homophobia among gay men. Internalized gay ageism is positively associated with depressive symptoms. One's sense of "mattering" offsets the health effect of internalized gay ageism. Internalized gay ageism is a unique, underexplored form of sexual minority stress.